Demonstration and interpretation of "scutoid" cells formed in a quasi-2D soap froth - Hutzler, Stefan; Weaire, Denis; Mughal, A.; Cox, S.J.; Burke, S.R. (My University, 2018)
Recently a novel type of epithelial cell has been discovered and dubbed the ‘scutoid’. It is induced by curvature of the bounding surfaces. We show by simulations and experiments that such cells are to be found in a dry foam subjected to this boundary condition.
PUBLISHED
Keywords: Quasi-2D foams; Scutoid; Epithelial cells; T1 transition; Nanoscience & Materials; EPITHELIAL CELLS; soft matter physics (foams, liquid crystals)